NOMAD CAMELS: Configurable Application for Measurements, Experiments and Laboratory Systems - Fuchs, Alexander; Lehmeyer, Johannes; Junkes, Heinz; Weber, Heiko B.; Krieger, Michael (Journal of Open Source Software, 2024)

NOMAD CAMELS - Configurable Application for Measurements, Experiments and Laboratory Systems - Lehmeyer, Johannes; Fuchs, Alexander; Krieger, Michael; Weber, Heiko B. (2021)

Optical and electrical studies on the TS defect in 4H-SiC - Lehmeyer, Johannes; Fuchs, Alexander; Li, Zhengming; Bornträger, Titus; Candolfi, Fabio; Schober, Maximilian; Fischer, Marcus; Hartmann, Martin; Neu, Elke; Bockstedte, Michel; Krieger, Michael; Weber, Heiko B. (Journal of Physics D-Applied Physics, 2024)
When annealing a 4H silicon carbide (SiC) crystal, a sequence of optically active defect centers occurs among which the TS center is a prominent example. Here, we present low-temperature photoluminescence analyses on the single defect level. They reveal that the three occurring spectral signatures TS1, TS2 and TS3 originate from one single defect. Their polarization dependences expose three different crystallographic orientations in the basal plane, which relate to the projections of the nearest neighbor directions. Accordingly, we find a three-fold level-splitting in ensemble studies, when applying mechanical strain. This dependency is quantitatively calibrated. A complementary electrical measurement, deep level transient spectroscopy, reveals a charge transition level of the TS defect at 0.6 eV above the valence band. For a future identification, this accurate characterization of its optical and electronic properties along with their response to mechanical strain is a mileston

Strain-Dependent Photoluminescence Line Shifts of the TS Color Center in 4H-SiC - Lehmeyer, Johannes; Fuchs, Alexander; Bornträger, T.; Popp, Matthias Albert; Weber, Heiko B.; Krieger, Michael (Defect and Diffusion Forum, 2023)
We present a detailed study of the behavior of the photoluminescence (PL) of the TS color center in 4H-SiC under controlled mechanical strain. We have investigated the TS1 line under varying strain, including its reaction to compression and tension. We use emission polarization measurements to gain access to the orientation of the underlying defects. We put our results in context with previous findings and find good agreement, corroborating the proposed microscopic model.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Color Center; Mechanical Strain; Photoluminescence; Photophysics

The Squeezable Nanojunction as a tuneable light-matter interface for studying photoluminescence of 2D materials - Popp, Matthias Albert; Kohring, Malte; Fuchs, Alexander; Korn, Sascha; Moses Badlyan, Narine; Maultzsch, Janina; Weber, Heiko B. (2D Materials, 2021)